Dynamical Behaviors of Snow Particles in the Saltation Layer - Araoka, Kuniaki; Maeno, Norikazu (1981)
P(論文) A photographic technique was developed to analyze dynamical behaviors of saltating particles in blowing snow. Each photograph taken with this technique can give information of trajectories of flying snow particles as well as their velocities and accelerations at each height. The analyses have shown that horizontal drag the surrounding air flow exerts on saltating particles is of Stokes type and the drag coefficient C_D can be represented as C_D=N/Re where Re is the Reynolds number and N is numerical constant ranging from 0.6 to 9. As for vertical motions a substantial downward force was found to act on a snow particle at the time of both its ascent and descent; Ascending snow particles did not reach the maximum height <υ_0>^2/2g where υ_0 and g are respectively the initial vertical velocity and the acceleration of gravity, and the maximum heights measured were smaller than those calculated by taking account of drag due to the surrounding air. departmental bulletin paper